Effects of different volumes of inhomogeneous medium to the radial dose and anisotropy functions in HDR brachytherapy. (March 2020) - Ab Shukor, N S; Musarudin, M; Abdullah, R; Abd Aziz, M Z
Abstract: The aim of this study is to study the effects of non –homogenous region closer to the HDR Brachytherapy source. Radial widths of 1, 3 and 5 cm of an inhomogeneous cylindrical area filled with bone and lung tissue in a water phantom are modelled in this study. The effects of this inhomogeneity to the g(r) and F(r, θ) of Nucletron 192 Ir microSelectron HDR source are assessed. The results show that the assumption of homogeneous water leads to underestimation of the bone dose by the treatment planning system. Meanwhile, overestimation of the dose is observed in the surrounding area. A relative difference of up to 19% is calculated for the largest bone volume. Contrast results are observed for the lung inhomogeneity model. A relative difference of up to 12% is observed in the lung dose. The presence of inhomogeneous region in the water phantom affects the anisotropy function; at a radial distance greater than 5 cm. Our results indicate that the presence of bone and lung inside the water phantom affect the g(r) and F(r, θ) in HDR brachytherapy. The degree of the effects depends on the material, position and volume of the inhomogeneity area.